PENGARUH PEMBANGUNAN INFRASTRUKTUR TERHADAP PERTUMBUHAN EKONOMI DI PROVINSI BENGKULU - Azuwandri, Azuwandri; Ekaputri, Retno Agustina; Sunoto, Sunoto (Fakultas Ekonomi Universitas Dehasen Bengkulu, 2019)
The purpose of this study was to Analyze Effects of Long Road Infrastructure Development, Energy Electricity, Telephone and Water to Economic Growth. The analytical method used to achieve this goal is by using PLS regression analysis model Fixed Effects. Type of key data used secondary data is district / municipality located in the province of Bengkulu years 2009?2013. The result using 7.0 eviews Program found that the factors positively and significantly affect economic growth during the years 2009?2013 Bengkulu province is the observation variable length Roads, Energy and Water, although variable Phone has a negative correlation, but a significant impact on economic growth.